Impaired Growth during Childhood in Patients with Primary Ciliary Dyskinesia. (12th December 2013) - Svobodová, Tamara; Djakow, Jana; Zemková, Daniela; Cipra, Adam; Pohunek, Petr; Lebl, Jan
Abstract : Primary ciliary dyskinesia (PCD) leads to recurrent/chronic respiratory infections, resulting in chronic inflammation and potentially in chronic pulmonary disease with bronchiectasis. We analyzed longitudinal data on body length/height and body mass index (BMI) for 29 children and young adults with PCD aging 1.5–24 years (median, 14.5) who had been diagnosed at the age of 0.5–17 years (median, 8). Of these, 10 carried pathogenic mutations in either DNAH5 or DNAI1 . In children with PCD, body length/height progressively decreased from + 0.40 ± 0.24 SDS (the 1st birthday), + 0.16 ± 0.23 SDS (3 years old), and - 0.13 ± 0.21 SDS (5 years old) to - 0.54 ± 0.19 SDS (7 years old; P = 0.01 versus 0 ), - 0.67 ± 0.21 SDS (9 years old; P = 0.005 versus 0 ), - 0.52 ± 0.24 SDS (11 years old; P = 0.04 versus 0 ), and - 0.53 ± 0.23 SDS (13 years old; P = 0.03 versus 0 ). These results reflect low growth rates during the childhood growth period. Thereafter, heights stabilized up to the age of 17 years. The growth deterioration was not dependent on sex or disease severity but was more pronounced in DNAH5 or DNAI1 mutation carriers. BMI did not differ from population standards, which suggests that nutritional deficits are not the cause of growth delay. We conclude that PCD leads to chronic deprivation with significant growth deterioration during childhood.